Principal Leadership Strategies In Shapeing Student Personality In Madrasah Ibtidaiyah Negeri 2 Mataram - Badrun Badrun; Sopian Hidayatullah; Fakhrurrazi Fakhrurrazi (Jurnal Bahana Manajemen Pendidikan, 2022)
The purpose of the study was to describe the planning, implementation and supervision of school principals in shaping the personality of students at Madrasah Ibtidaiyah Negeri 2 Mataram. This research uses a case study approach. This research is included in the field research category. This study uses a qualitative research approach. Research data collection is done by observation, interviews and documentation studies. Research results (1). The Principal's Leadership Strategy in shaping the student's personality by planning the character to be formed, the personality formation strategy, the formation of the student's character based on the student's development, the factors considered in the formation of the student's personality and the Principal's leadership strategy in carrying out responsible activities. (2) Implementation of the Principal in shaping students' personalities, with several programs, namely: Intensive teacher development, involving teachers in shaping students' personalities and developing school culture. (3). The Principal's strategy in shaping the student's personality is carried out by controlling the personality of teachers and students, controlling the principal in supervising the teacher's role and controlling the principal in observing the teacher's efforts and involving the teacher in supervision.